Adaptive optics in single objective inclined light sheet microscopy enables three-dimensional localization microscopy in adult Drosophila brains - Hung, Shih-Te; Llobet Rosell, Arnau; Jurriens, Daphne; Siemons, Marijn; Soloviev, Oleg; Kapitein, Lukas C.; Grußmayer, Kristin; Neukomm, Lukas J.; Verhaegen, Michel; Smith, Carlas (Frontiers in Neuroscience, 2022)
Single-molecule localization microscopy (SMLM) enables the high-resolution visualization of organelle structures and the precise localization of individual proteins. However, the expected resolution is not achieved in deep tissue as the imaging conditions deteriorate. Sample-induced aberrations distort the point spread function (PSF), and high background fluorescence decreases the localization precision. Here, we synergistically combine sensorless adaptive optics (AO), in-situ 3D-PSF calibration, and a single-objective lens-inclined light sheet microscope (SOLEIL), termed (AO-SOLEIL), to mitigate deep tissue-induced deteriorations. We apply AO-SOLEIL on several dSTORM samples including brains of adult Drosophila. We observed a 2x improvement in the estimated axial localization precision while we used a synergistic solution concerning widefield without aberration correction. Thus AO-SOLEIL enhances the overall imaging resolution and further facilitates the visualization of subcellular and molecular characterizations in tissue.